Group Exhibition-Art Athina, The Museum of Forgetting, Palaio Faliro Greece - Antoniou, Klitsa (My University, 2026)
Art Athina, The Museum of Forgetting, Palaio Faliro Greece Atlantropa Series: But the Sea Kept Turning Blank Pages Looking for History